Nicotine replacement therapy in pregnancy and major congenital anomalies in offspring - Dhalwani, Nafeesa N.; Szatkowski, Lisa; Coleman, Tim; Fiaschi, Linda; Tata, Laila J. (American Academy of Pediatrics, 2015)
BACKGROUND AND OBJECTIVES: Nicotine replacement therapy (NRT) is now being used as a smoking cessation aid during pregnancy, although little is known about fetal safety. We assessed the relationship between early pregnancy exposure to NRT or smoking with major congenital anomalies (MCA) in offspring.